THE DEVELOPMENT OF LEARNING ACHIEVEMENT IN ENGLISH READING COMPREHENSION BY SQ4R TECHNIQUE FOR 5TH GRADE STUDENTS, WATTAMMAKASET SCHOOL - Saengern, Natcha; thanaphatchottiwat, Suphornthip (Journal of Buddhist Education and Research (JBER), 2023)
The purposes of the research were to: 1) to compare the achievement in English reading comprehension for 5th Grade Students through the SQ4R technique and 2) to explore the student’s satisfaction to English subject after being taught by using the SQ4R technique. The samples were 24 5th Grade Students of Wattammakaset school who were studying in the second semester, academic year 2021. The samples were selected by Purposive Sampling. The research instruments used were: 1) 13 learning management plan using SQ4R technique, 2) achievement test for English reading comprehension proficiency and 3) student satisfaction questionnaire in studying English by SQ4R technique. The statistics used for data analysis were: mean, standard deviation and t-test. The findings of the research were as follows: 1) the post-learning English reading comprehension proficiency achievement was higher than the pre-learning when using SQ4R technique with the statistical significance at the .05 level. 2) students’ satisfaction with SQ4R technique was at the high level.